Tungsten disulfide-chitosan film as optical pulse and amplitude modulator in C-band region - Ahmad, Harith; Ooi, Shok Ing; Yusoff, Norazriena; Lim, Hwee San; MatJafri, Mohd Zubir; Thambiratnam, Kavintheran; Tiu, Zian Cheak (IOP Publishing, 2019)
A tungsten disulfide (WS2)-Chitosan film based optical modulator for operation in the C-band region is demonstrated. The integration of the WS2-Chitosan film into an erbium doped fiber laser cavity reveals high optical pulse and amplitude modulation efficiency due to the substantial nonlinear absorption properties of the WS2-Chitosan film. The strong thermo-optic effect exhibited by the WS2-Chitosan film enables optical amplitude modulation, with modulation efficiencies of 0.10 dB mW-1 over a pump power ranging from 0.01 mW to 130.10 mW. The proposed WS2-Chitosan based optical modulator has significant potential for integration and application into a multitude of optoelectronic systems. © 2019 Astro Ltd.